2012
DOI: 10.1002/nau.21217
|View full text |Cite
|
Sign up to set email alerts
|

Loss of bladder smooth muscle caveolae in the aging bladder

Abstract: Biological aging significantly decreases BSM caveolae number and morphology with associated selective alteration in caveolin protein expression. Since caveolae are protected membrane regions that regulate signal transduction, age-related alterations in caveolae and caveolin protein expression could alter BSM contractility resulting in bladder dysfunctions of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Caveolae are protected membrane regions that regulate signal transduction and are important for detrusor contractility. Rat studies have shown that aging significantly decreases bladder caveolae number and morphologic age-related alterations in caveolae and caveolin protein expression could alter bladder contractility (23). …”
Section: Discussionmentioning
confidence: 99%
“…Caveolae are protected membrane regions that regulate signal transduction and are important for detrusor contractility. Rat studies have shown that aging significantly decreases bladder caveolae number and morphologic age-related alterations in caveolae and caveolin protein expression could alter bladder contractility (23). …”
Section: Discussionmentioning
confidence: 99%
“…Among Americans 65 years and older, more than one-half have been diagnosed with three or more chronic conditions [13]. Common chronic conditions such as diabetes mellitus are known to predispose individuals to UAB, while animal studies discussed below indicate that chronic ischemia commonly seen in the context of atherosclerosis and microvascular disease [14], a profound lack of estrogen seen in some postmenopausal women [15][16][17][18] or biological processes, which are intrinsic to aging [17,19] could also potentially contribute to UAB by favoring the development of degenerative or biochemical changes involving key components of the detrusor muscle, its contractile machinery or its innervation. For example, there is a striking paucity of studies that would permit an examination of the relationship between menopause or estrogen status and UAB or DU.…”
Section: Current Understanding Of Uab Pathophysiologymentioning
confidence: 99%
“…For example, there is a striking paucity of studies that would permit an examination of the relationship between menopause or estrogen status and UAB or DU. At the same time, studies using mature or aged animal models have shown that prolonged consequences of bilateral ovariectomy include relevant consequences such as axonal [18] and myocyte [18] degeneration as seen in older adults with UAB [20]; depletion of caveolae [17] with potential implications for age-associated changes in calcium signaling [19,21] and declines in key proteins involved in smooth muscle contractility [16].…”
Section: Current Understanding Of Uab Pathophysiologymentioning
confidence: 99%
“…Among Americans 65 years and older, more than one-half have been diagnosed with three or more chronic conditions [13]. Common chronic conditions such as diabetes mellitus are known to predispose individuals to UAB, while animal studies discussed below indicate that chronic ischemia commonly seen in the context of atherosclerosis and microvascular disease [14], a profound lack of estrogen seen in some postmenopausal women [1518] or biological processes, which are intrinsic to aging [17, 19] could also potentially contribute to UAB by favoring the development of degenerative or biochemical changes involving key components of the detrusor muscle, its contractile machinery or its innervation. For example, there is a striking paucity of studies that would permit an examination of the relationship between menopause or estrogen status and UAB or DU.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is a striking paucity of studies that would permit an examination of the relationship between menopause or estrogen status and UAB or DU. At the same time, studies using mature or aged animal models have shown that prolonged consequences of bilateral ovariectomy include relevant consequences such as axonal [18] and myocyte [18] degeneration as seen in older adults with UAB [20]; depletion of caveolae [17] with potential implications for age-associated changes in calcium signaling [19, 21] and declines in key proteins involved in smooth muscle contractility [16]. …”
Section: Introductionmentioning
confidence: 99%